СТРАТЕГІЯ БАНКУ ЩОДО УПРАВЛІННЯ КАНАЛАМИ ЗБУТУ НА РОЗДРІБНОМУ РИНКУ (Світ фінансів, 2017)
Голуб В. Ф. Стратегія банку щодо управління каналами збуту на роздрібному ринку. Розглянуто питання розробки стратегії банку на роздрібному ринку щодо управління каналами збуту. Визначено основні завдання стратегії управління каналами збуту банківських продуктів на роздрібному ринку, обґрунтовано критерії вибору каналів збуту, доведено доцільність інтеграції системи каналів збуту. Hjlub V. The strategy of bank as for the management of the sales channels on the retail market. Questions of development of strategy of bank in the retail market concerning management of trade channels are considered. The basic tasks of strategy of management by trade channels of bank products in the retail market are determined, criteria of a choice of system of trade channels are substantiated, the expediency of integration of system of trade channels is proved.